2001
DOI: 10.2337/diabetes.50.11.2481
|View full text |Cite
|
Sign up to set email alerts
|

Antecedent Hyperglycemia, Not Hyperlipidemia, Is Associated With Increased Islet Triacylglycerol Content and Decreased Insulin Gene mRNA Level in Zucker Diabetic Fatty Rats

Abstract: Type 2 diabetes is caused by a combination of ␤-cell dysfunction and insulin resistance. Over time, hyperglycemia worsens, a phenomenon that has been attributed to deleterious effects of chronic hyperglycemia (glucotoxicity) or chronic hyperlipidemia (lipotoxicity) on ␤-cell function and is often accompanied by increased islet triacylglycerol (TAG) content and decreased insulin gene expression. To examine these two potentially pathogenic forces, we studied Zucker rats (leptin receptor wild type, ؉/؉; heterozyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
88
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(99 citation statements)
references
References 48 publications
9
88
0
2
Order By: Relevance
“…The deleterious effect of high glucose is well established [2,3], but increased NEFA at physiological glucose concentrations were also able to significantly alter GSIS and insulin content. These results are in accordance with previous studies [6,10,33], but argue against the hypothesis that increased glucose is a prerequisite for the deleterious effect of NEFA on betacell function [11,12,13,14]. We also found that in-action is, at least in part, mediated by modifications in gene expression [9,17].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The deleterious effect of high glucose is well established [2,3], but increased NEFA at physiological glucose concentrations were also able to significantly alter GSIS and insulin content. These results are in accordance with previous studies [6,10,33], but argue against the hypothesis that increased glucose is a prerequisite for the deleterious effect of NEFA on betacell function [11,12,13,14]. We also found that in-action is, at least in part, mediated by modifications in gene expression [9,17].…”
Section: Discussionsupporting
confidence: 91%
“…However, whether glucose and NEFA alter beta-cell function synergistically or separately, remains controversial. Some authors have shown that beta-cell failure was induced by increased glucose alone [2,9] or increased NEFA alone [6,10], while others have suggested that excess glucose or NEFA are not deleterious separately, but synergize in causing glucolipotoxicity [11,12,13,14].…”
mentioning
confidence: 99%
“…Previously it has been shown that inhibition of fatty acid oxidation by an inhibitor of CPT1 reduces basal hypersecretion in ZDF rats, such that the maintenance of fatty acid oxidation may also be important in compensation processes [38]. Islets of the ZF rat displayed none of the well-described features of lipotoxicity [7,[39][40][41][42][43]. The TG content was mildly decreased rather than dramatically increased [7,40].…”
Section: Discussionmentioning
confidence: 93%
“…It is well documented that LEPR-deficiency, independent of strain, causes a defect in glucose-stimulated insulin secretion, both in the intact rodent [38] and in isolated islets [39]. Moreover, the increased insulin concentrations in the fed and fasting states of obese mice of both strains indicate that insulin resistance is the primary cause of glucose intolerance in LEP-and LEPR-deficient mice ( Table 1 ).…”
Section: Discussionmentioning
confidence: 94%